Ekologo-legal regulation of rational use of land resources - Одарюк, О. О. (Scientific Progress & Innovations, 2013)
The analysis of increase of use of natural resources by man and its influence on self-reproduction of biosets is carried out. Advantages of ekologo-landscape land management in system of territorial planning of agricultural land tenure in comparison with traditional methods of the organization of territory are proved. The necessity of creation of information base of formation of ecological factors of use of land resources is considered. The adverse action of degradation processes and their impact on agriculture is analyzed.